Pembentukan Karakter Religius Melalui Pembelajaran Berbasis HOTS (Higher Order Thinking Skill) Pada Mata Pelajaran PAI - Ade Yuliyanti; Susi Kusmiyati (Departement of Mathematics Education, 2024)
HOTS (Higher Order Thinking Skill) based learning is really needed by students because real life problems are very complex, unstructured, new complexity so they require thinking skills that go beyond just applying what has been learned. This critical way of thinking is a demand in today's era, which has entered the era of society 5.0, where humans all rely on technology as part of their lives. Initially the internet was a medium of information, but now it is used as a means of living everyday life. To anticipate bad influences that come in various directions, students must have maturity in thinking, so starting from this problem students need to be developed to solve problems that exist in students' lives so that they can integrate them into everyday life. This research method uses the classroom action research method (Classroom Action Research). Three cycles were carried out with four meetings, each cycle consisting of four research steps, namely planning, implementation, observation and reflection. This research focuses on learning carried out by PAI teachers, namely HOTS-based learning with the aim of forming the religious character of students at SMA Negeri I Cikijing. The data analysis technique uses descriptive analysis. The research results obtained (1) an increase in students' learning activities (2) an increase in high-level thinking abilities (Hots) (3) a formation of students' character in accordance with the Syajaah material (dare to defend the truth)